2017
DOI: 10.1111/cag.12427
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of Aboriginal peoples in Newfoundland and Labrador: Memorial's first‐year students (2013) speak

Abstract: Key Messages When invited to identify what they know about Aboriginal people, Memorial students reveal racism and stereotypes, and cannot describe the specificity and diversity of Aboriginal peoples in Canada. Those able to perform best on our test tend to be less prejudiced. Although the students perform badly on our test, most consider it a good measure of their knowledge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…Recent research has demonstrated that culturally relevant pedagogy that generates teaching, curricula, and texts in which students see themselves, their experiences, and their history fosters engaged learners (Ladson-Billings 1998. Our findings here, in the Queen's University pilot study (Godlewska et al 2013), and in our qualitative analysis of the Memorial University data (Godlewska et al 2017b, this issue) also suggest non-Aboriginal students do not see Aboriginal people, cultures, or histories as part of their own landscape.…”
Section: Current Events Students Performed Relativelysupporting
confidence: 58%
See 3 more Smart Citations
“…Recent research has demonstrated that culturally relevant pedagogy that generates teaching, curricula, and texts in which students see themselves, their experiences, and their history fosters engaged learners (Ladson-Billings 1998. Our findings here, in the Queen's University pilot study (Godlewska et al 2013), and in our qualitative analysis of the Memorial University data (Godlewska et al 2017b, this issue) also suggest non-Aboriginal students do not see Aboriginal people, cultures, or histories as part of their own landscape.…”
Section: Current Events Students Performed Relativelysupporting
confidence: 58%
“…This sense of Indigenous people vanishing comes from many sources, including abiding 19 th ‐century ideology, well‐meaning concern for Indigenous cultural survival, perhaps a general sense of ecological decline in which Indigenous people tend to be clumped, and a more troubling sense of cultural superiority combined with a survival of the fittest mentality—all reinforced in the curriculum. This is discussed further in our analysis of the text responses to the questionnaire (Godlewska et al , this issue).…”
Section: Quantitative Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…One of the biggest concerns regarding the modern cultural suppression of Indigenous peoples in Canada is related to a blatant lack of understanding among the general population regarding the lives and history of Indigenous peoples, which in turn hinders public knowledge of the challenges specifically faced by Indigenous populations today. This knowledge gap was showcased by the results of The 2013 Aboriginal Awareness Survey conducted to assess knowledge of First Nations, Métis, and Inuit in Canada among three hundred and ten first year university students in Newfoundland and Labrador (Godlewska et al, 2017b;Godlewska, Schaefli, Massey, Freake, & Rose, 2017c). The questionnaire examined what the students have learned about Indigenous peoples, where they learned this information, and their social attitudes towards these groups.…”
Section: Public Perceptions Of Indigenous Peoples In Canadamentioning
confidence: 99%